2017
DOI: 10.3389/fmicb.2017.01172
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Inter-kingdom Communication by PhcBSR Quorum Sensing System in Ralstonia solanacearum Phylotype I Strain GMI1000

Abstract: Ralstonia solanacearum is a ubiquitous soil-borne plant pathogenic bacterium, which frequently encounters and interacts with other soil cohabitants in competition for environmental niches. Ralsolamycin, which is encoded by the rmy genes, has been characterized as a novel inter-kingdom interaction signal that induces chlamydospore development in fungi. In this study, we provide the first genetic evidence that the rmy gene expression is controlled by the PhcBSR quorum sensing (QS) system in strain GMI1000. Mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…1 , 3 ). Some previous studies have also revealed that R. solanacearum employs QS to control the production of ralsolamycin to achieve a fitness advantage in inter-kingdom competition [ 24 26 ]. Our new findings suggested that complicated mechanisms have evolved in R. solanacearum to achieve for a competitive advantage in the microbial community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 , 3 ). Some previous studies have also revealed that R. solanacearum employs QS to control the production of ralsolamycin to achieve a fitness advantage in inter-kingdom competition [ 24 26 ]. Our new findings suggested that complicated mechanisms have evolved in R. solanacearum to achieve for a competitive advantage in the microbial community.…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis of ralsolamycin in R. solanacearum is modulated by the two nonribosomal peptide synthetases, RmyA and RmyB [ 25 ]. Interestingly, our previous study revealed that the expression of rmyAB was controlled by the phcBSR QS system [ 26 ], suggesting that QS plays an important role in inter-kingdom communication between R. solanacearum and fungi. In this study, we showed that anthranilic acid produced by TrpEG in R. solanacearum inhibits sexual mating and hypha formation in Sporisorium scitamineum .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, mutants were generated with the pK18mobsacB based homologue recombination, by which target genes were in-frame deleted as described previously ( Li et al, 2017 ). In brief, coding sequence of target genes was removed by the joint PCR, which conjugated both ends of flanking DNA fragments.…”
Section: Methodsmentioning
confidence: 99%
“…R. solanacearum strains and F. oxysporum f. cubense FOC4 were dropped onto same PDA agar plate and incubated at 28°C for about eight days. When two kinds of colonies interweaved each other, the FOC4 mycelia surrounded the interaction zones at about 1 cm were harvested and subjected for chlamydospore counting under microscope ( Li et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation